Photometric Modeling and VIS‐IR Albedo Maps of Tethys From Cassini‐VIMS. Issue 13 (7th July 2018) - Filacchione, G.; Ciarniello, M.; D'Aversa, E.; Capaccioni, F.; Cerroni, P.; Buratti, B.; Clark, R. N.; Stephan, K.; Plainaki, C.
Abstract: We report about the derivation of visible (VIS) and infrared (IR) albedo maps and spectral indicators of Saturn's satellite Tethys from the complete Cassini‐Visual and Infrared Mapping Spectrometer (VIMS) data set. The application of a photometric correction is necessary to remove illumination and viewing effects from the I/F spectra, to compute spectral albedo and to correctly associate spectral variations to changes in composition or physical properties of the surface. In this work we are adopting the photometric correction proposed by Shkuratov et al. (2011, https://doi.org/10.1016/j.pss.2011.06.011 ) to derive albedo maps of Tethys from disk‐resolved Cassini‐VIMS data. After having applied a similar methodology to Dione's data (Filacchione et al., 2018, https://doi.org/10.1002/2017GL076869 ), we present here the results achieved for Tethys: surface albedo maps and photometric parameters are computed at five visible (0.35, 0.44, 0.55, 0.70, and 0.95 μm) and five infrared (1.046, 1.540, 1.822, 2.050, and 2.200 μm) wavelengths and rendered in cylindrical projection with a 0.5° × 0.5° angular resolution in latitude and longitude, corresponding to a highest spatial resolution of 4.7 km/bin. The 0.35‐ to 0.55‐ and 0.55‐ to 0.95‐μm spectral slopes and the water ice 2.050‐μm band depth maps are computed after having applied the photometric correction, in order to trace the leading‐trailing hemisphere dichotomy, to constrain the shape of the equatorial lens generated by the bombardment of high‐energy magnetospheric electrons on the leading hemisphere, and to observe the stronger water ice band depth and reddening within the floors of Odysseus and Penelope impact craters. Plain Language Summary: Visible and infrared albedo maps of Tethys surface are derived from Cassini‐Visual and Infrared Mapping Spectrometer data set by applying a photometric correction able to remove illumination and viewing effects from the data. This processing allows to build spectral indicator maps able to trace composition changes in terms of visible colors and water ice band depth across the surface. We focus our analysis on specific geologic features, including impact craters and low‐albedo areas, where exogenic processes are occurring. We report how E‐ring particles, magnetospheric and cold plasma particles bombardment, alter the surface of Tethys. Key Points: Computation of Tethys albedo maps at VIS and IR wavelengths by means of photometric correction Retrieval of visible spectral slopes and water ice band depth maps Study of the correlations between spectral maps and geomorphological features